2008
DOI: 10.1359/jbmr.080214
|View full text |Cite
|
Sign up to set email alerts
|

Trabecular Bone Deterioration in col9a1+/− Mice Associated With Enlarged Osteoclasts Adhered to Collagen IX–Deficient Bone

Abstract: ABSTRACT:Introduction: Short collagen IX, the exclusive isoform expressed by osteoblasts, is synthesized through alternative transcription of the col9a1 gene. The function of short collagen IX in bone was characterized in col9a1-null mutant mice. Materials and Methods: Trabecular bone morphometry of lumbar bones and tibias was evaluated by CT and nondecalcified histology. Osteoblastic and osteoclastic activities were evaluated by PCR-and microarraybased gene expression assays and TRACP-5b and C-terminal telope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 60 publications
1
24
0
Order By: Relevance
“…In the Atlantic salmon, COL11A2 is expressed throughout the notochord in early stages of development, but quickly becomes confined to the segmented, non-mineralizing regions of the notochord, suggesting a similar role for COL11A2 in inhibiting mineralization [87]. COL9A1 may have a role in postnatal bone maintenance, as COL9A1 +/− and −/− mice develop osteoporosis in association with an increased osteoclast number and activity in trabecular bone [88]. Additionally, mutations in COL9A1 , COL9A2 , and COL9A3 may cause multiple epiphyseal dysplasia, which is characterized by abnormal ossification of the epiphyses [89].…”
Section: Osteoblast Physiology and Altered Bone Mineralization In mentioning
confidence: 99%
“…In the Atlantic salmon, COL11A2 is expressed throughout the notochord in early stages of development, but quickly becomes confined to the segmented, non-mineralizing regions of the notochord, suggesting a similar role for COL11A2 in inhibiting mineralization [87]. COL9A1 may have a role in postnatal bone maintenance, as COL9A1 +/− and −/− mice develop osteoporosis in association with an increased osteoclast number and activity in trabecular bone [88]. Additionally, mutations in COL9A1 , COL9A2 , and COL9A3 may cause multiple epiphyseal dysplasia, which is characterized by abnormal ossification of the epiphyses [89].…”
Section: Osteoblast Physiology and Altered Bone Mineralization In mentioning
confidence: 99%
“…However, a mouse model with collagen IX deficiency (Col9a1À/Àmice) showed compromised development [Dreier et al, 2008] and maturation [Opolka et al, 2007] of cartilage. Haploinsufficiency of collagen IX (Col9a1þ/Àmice) caused abnormally flattened and enlarged osteoclasts, potentially impairing catabolic bone remodelling [Wang et al, 2008]. Although lack of type IX collagen is associated with early onset osteoarthritis [Fassler et al, 1994], increased severity of arthritis [Carlsen et al, 2006], and multiple epiphyseal dysplasia [Czarny-Ratajczak et al, 2001], our patients have not as yet developed cartilage disorders.…”
Section: Phenotype Of 6q11-q14 Interstitial Deletionsmentioning
confidence: 88%
“…Type X collagen may increase the tensile strength of interface tissues such as peri-implant bone. In addition, a study on Col9 knockout bone showed significantly increased susceptibility to osteoclastic bone resorption (Wang et al, 2008). The long-term resistance of peri-implant bone against catabolic remodeling might be contributed, in part, by its unique ECM composition.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%